Research progress on nanotoxicity and detoxification of cobalt in metal-based implants - Wentao Fan; Mingxin Guo (Annals of Medicine)
Background Cobalt nanoparticles (CoNPs), a primary wear debris from joint prostheses, exhibit significant cytotoxicity. This review aims to synthesize current understanding of CoNPs’ toxicity mechanisms, their local and systemic pathological effects, the emerging role in ferroptosis, potential detoxification strategies, and outline critical future research directions.Discussion CoNPs are internalized by cells, primarily via phagocytosis, and undergo lysosomal degradation. This process triggers substantial reactive oxygen species (ROS) generation, a key mechanism driving cytotoxicity and cell death pathways. Locally, at the implant site, CoNPs contribute to adverse outcomes including aseptic inflammation, osteolysis, and inflammatory pseudotumor formation. Furthermore, systemically disseminated CoNPs pose risks to distant organs, with potential impairments reported in liver, kidney, cardiac, thyroid, and neurological functions. Emerging evidence specifically implicates CoNPs in inducing ferroptosis, an iron-dependent form of regulated cell death. Current research explores various strategies for mitigating CoNPs toxicity.Conclusions CoNPs released from joint prostheses present substantial local and systemic health hazards. Their toxicity is primarily mediated through lysosomal degradation, ROS overproduction, and the induction of cell death, including ferroptosis. While mechanisms are increasingly understood, further research is crucial to fully elucidate the long-term systemic consequences and to develop effective clinical detoxification and preventative strategies for patients with cobalt-containing implants.